Pengaruh Penyakit Penyerta Kehamilan dan Kehamilan Ganda dengan Kejadian Bayi Berat Lahir Rendah di RSUD Arifin Achmad Provinsi Riau - Ani Triana (STIKes Hang Tuah Pekanbaru, 2014)
Of data obtained from the Medical Records General Hospital Arifin Achmad Riau from 2011 to 2013 for that is LBW in 2011 registered 46 cases (1.62%) of 2833 deliveries, 179 cases registered in 2012 (5.44%) of the 3290 labor and in 2013 registered 130 cases (4.56%) of 2848 births and LBW are still included in 3 of the 15 diseases causing neonatal mortality. Purpose of research is known factors related to LBW in General Hospital Arifin Achmad Riau Year 2011- 2013. Design of research is case-control study. The case is infat born to LBW in General Hospital Arifin Achmad Riau in 2011-2013 equal 355 respondent and control is infants born to normal birth weight in General Hospital Arifin Achmad Riau in 2011-2013 equal 355 respondent. The results of research maternal to Accompanying Disease Pregnancy is more risk of giving birth to LBW 10 times (95% CI 6.2 -16.6) and maternal to more risk of having a multiple pregnancy to LBW 15 times (95% CI 4,8- 45.1). Conclusion that is the independent variables have causal relations with incidence of LBW is Age, Accompanying Disease Pregnancy, Preeclampsia/eclampsia, Multiple pregnancy, PROM, Hydramnion, Plasenta Previa. Advice is intended for health professionals that is active in counseling, the General Hospital Arifin Achmad Riau need liveliness LBW prevention